2010
DOI: 10.3802/jgo.2010.21.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to Papanicolaou smear screening in Korean women: Korean National Health and Nutrition Examination Survey 2005

Abstract: Objective: This study was conducted to provide a nationwide analysis on barriers to cervical cancer screening in Korea. Methods: Data used for this study was obtained in a survey called Korean National Health and Nutrition Examination Survey (KNHANES) 2005, which collected data from 2,590 Korean women aged older than 21 years who had not had a hysterectomy and were eligible for Papanicolaou (Pap) smears. Multivariate analysis was adopted to control each demographic factor and unhealthy behavior variable. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Consistent with previous studies of cancer screening (Kwon et al, 2009;Lee et al, 2010;Park et al, 2010), our results indicate that education level is significantly associated with the gastric cancer screening rate. By contrast, monthly household income did not reach statistical significance in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with previous studies of cancer screening (Kwon et al, 2009;Lee et al, 2010;Park et al, 2010), our results indicate that education level is significantly associated with the gastric cancer screening rate. By contrast, monthly household income did not reach statistical significance in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 82%
“…The result of study with the title "The causes of not doing Pap smear" showed that 55.1 percent of women who have been tested regularly 36 years old and most women who were not tested until now have been often aged 25 years or less (Park and Park, 2010). Results of other study that demonstrated that older people are doing routinely Pap smears more than young which was in according to our study (Jalilian and Emdadi, 2011).…”
Section: Resultssupporting
confidence: 69%
“…Firstly, greater exposure to risk factors for cervical cancer in the low socioeconomic group than in the higher SES group; secondly, the lower participation rate of the low socioeconomic group in the cervical cancer screening program. Previous studies have shown that the participation rate in cervical cancer screening was low in women with low education levels13,14) or unmarried women 14,15). Thirdly, the lower socioeconomic groups' lower accessibility to the medical care system 16).…”
Section: Discussionmentioning
confidence: 97%